The Influence of Leadership as Moderating Variable Among Strategy Execution and Organizational Performance in Jordanian Public Sector - Farhan, Hodifah; Owaidha, Abu; Anuar Azmin, Adi (International Journal of Engineering and Technology, 2018)
This paper aims to analyse the effect of leadership on the relationship between strategy execution and organizational performance of organizations in public sector in Jordan. The framework explores the dimensions of some constructs and their effects on organizational performance. The proposed constructs of independent variables are organizational level of analysis (organizational structure, o, organizational culture, reward system and external consultant), execution plan (execution objectives, execution tasks, and execution responsibility) and leadership. Specifically, leadership was tested as a moderator. In this quantitative research, cross-sectional data of administrative officer working in 30 ministries of the Jordanian government were obtained. The total respondents were 137 and all of them work as administrative officer in public organizations in Jordan. This research uses of data analysis in SEM (Structure Educational Modeling) using the Partial Least Square 2.0. The results obtained showed a moderator effect of leadership on the relationship between (organizational structure, o, organizational culture, reward system and external consultant), and organizational performance, the study found the Leadership will moderate on the relationship of organizational structure, organizational culture, reward system and external consultant towards organizational performance in Jordanian public sector.Â Â